(untitled) (Journal of Applied Oral Science, 2022)
Objective: The objective of this retrospective study was to evaluate the impact of myofascial trigger points (MTrPs) in patients with articular disc displacement with reduction (DDWR) and to identify which clinical variables are associated with the concomitant presence of DDWR and MTrPs. Material and Methods: 130 patients were selected that sought treatment due to joint pain, with ages ≥18 years, of both genders, with DDWR confirmed by magnetic resonance imaging. The sample was divided into two groups: Group 1, patients with DDWR and MTrPs (N=101); and Group 2, patients with DDWR and no MTrPs (N=29). Information on gender, age, pain duration, pain scores, and maximal interincisal distance (MID) were collected. The logistic regression model was used and the odds ratios (OR) was calculated (p<0.05). Results: Group 1 presented statistically significant higher mean pain scores (p=0.007), and smaller MID (p=0.0268) than Group 2. OR were significant for the pain scores (1.429), MID (0.937) and gender (women) (2.810). Conclusions: Patients with DDWR and MTrPs had increased pain scores and a MID decrease compared to patients with DDWR and no MTrPs. The variables pain scores, MID, and gender (women) showed a significant association with the concomitant presence of DDWR and MTrPs.